Sirolimus-eluting stent treatment for unprotected versus protected left main coronary artery disease in widespread clinical routine: 6-month and 3-year clinical follow-up results from the prospective multicentre German Cypher Registry. Issue 10 (21st September 2007) - Khattab, Ahmed A; Hamm, Christian W; Senges, Jochen; Toelg, Ralph; Geist, Volker; Bonzel, Tassilo; Kelm, Malte; Levenson, Benny; Neumann, Franz-Josef; Nienaber, Christoph A; Pfannebecker, Thomas; Sabin, Georg; et al.
Abstract : Background: Percutaneous coronary intervention (PCI) of left main coronary artery (LMCA) disease in the bare stent era was limited by high restenosis rates which eventually resulted in sudden death in unprotected cases. Clinical and angiographic restenosis has been substantially reduced by drug-eluting stents, reviving therefore this indication for PCI despite the absence of direct comparative studies with coronary artery bypass graft surgery. Objective: To assess the acute, mid- and long-term outcomes of patients treated with sirolimus-eluting stents for unprotected LMCA stenoses and to compare them with those treated for protected LMCA disease in the same time period from the German Cypher Registry. Setting and patients: The German Cypher Registry included 6755 patients. Eighty-two patients treated for unprotected LMCA disease were compared with 118 patients treated for protected LMCA stenoses. All patients were treated by sirolimus-eluting stents. The primary end point was death, myocardial infarction (MI) and target vessel revascularisation at 6 months' follow-up. Survival free of MI at the long term was considered as the safety end point. Results: One-third of the patients in both groups were treated for the distal left main bifurcation. Angiographic success was 98.5% for both groups. The cumulative combined incidence of all-cause death, non-fatal MI and target vessel revascularisation at 6 months was 14.1% in the unprotected LMCA group and 13.1% in the protected group (hazard ratio = 0.81 (95% CI 0.37 to 1.74), p = 0.8). At long-term, death/MI were reported among 20.2% (95% CI 13.5% to 29.6%) of the protected group versus 11.8% (95% CI 6.3% to 21.4%) of the unprotected group (p = 0.2). Conclusion: Sirolimus-eluting stent treatment of unprotected and protected LMCA stenoses is technically feasible in widespread routine clinical use. Acceptable long-term clinical results can be achieved, with no particular safety concerns about treatment of unprotected LMCA disease.